STRATEGI BAURAN PEMASARAN PRODUCT, PRICE, PEOPLE, DAN PROCESS TERHADAP KEPUTUSAN MENGGUNAKAN JASA EKSPEDISI (STUDI KASUS PADA “KIRIMAJA” PT. AEROJASA CARGO) - Humaira, Salsabila Annisa; Agung, Maulana (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
Abstract Strategy is a set of decisions and actions in achieving goals and managing resources according to opportunities and threats. This study aims to analyze the influence of products, prices, people and processes on the decision to use the services of PT. Aerojasa Cargo. This study used a qualitative research method with a descriptive design and used 3 data collection techniques, namely observation, interviews and documentation. The results of this study indicate that the product strategy is indicated by a better product, namely standard service, next-day service and same-day service, people (HR) strategy to implement empowerment and training programs, and process strategy using technology, fast service and efficient.